Tema-Tema Penelitian Pendidikan: Inspirasi dan Motivasi Bagi Guru Madrasah Ibtidaiyah - Maimun, Agus (Madrasah: Jurnal Pendidikan dan Pembelajaran Dasar, 2020)
Research activities are basically part of teacher responsibilities in education. This confirms the statement, the task of the teacher is not only as an educator and teacher, but also as a researcher. As researchers, teachers must have research competencies. This writing will discuss the role of the headmaster in developing a culture of research in Madrasah Ibtidaiyah, the ability of teachers to find research problems that are relevant to their scientific fields in Madrasah Ibtidaiyah, and research space and research themes on education in Madrasah Ibtidaiyah. This paper discusses experiments and empirical practices using the reflective discussion method, which combines telling with deduction thinking with induction. This paper is expected to help teachers or students of Madrasah Ibtidaiyah Teacher Education (PGMI) to more easily find problems or research themes that can be formulated into research titles and can easily conduct research properly. The writing shows that the madrasah headmaster needs to develop a strategic program that allows the growth of a facilitating culture among MI teachers. Research issues relevant to the field of teacher science can be sought and obtained from various sources, published: application of theory, studies that can be replicated, clarification of contradictory findings, literature review, individual experiences, and electronic mailing lists. Many scopes and research themes can be formulated as research titles, published: intra-curricular, supplementary curricular, madrasah management, madrasah related, madrasah leadership, education personnel, student issues, and the relationship between madrasa and related relationships. For this reason, something that must be done by policy makers in Madrasah Ibtidaiyah always encourages and facilitates teachers to conduct research. Specific research that makes a significant contribution to improving the quality and outcomes of education and learning.